A novel mechanical-electric-hydraulic power coupling electric vehicle considering different electrohydraulic distribution ratios. (1st December 2021) - Hong, Jichao; Ma, Fei; Xu, Xiaoming; Yang, Jian; Zhang, Hongxin
Graphical abstract: Highlights: A novel mechatronics-electro-hydraulic power coupling system is proposed. An electro-hydraulic ratio distribution method is proposed targeted on the electric torque. Different distribution ratios are discussed for torque and energy-saving characteristics. The optimal ratios are determined with battery state of charge as the constraint. The practical engineering application potentials are verified on actual driving conditions. Abstract: The engagement and distribution ratio of electric and hydraulic power will certainly affect the stability and efficiency of the mechatronic-electro-hydraulic power coupling (MEHPC) system. This paper proposes a novel MEHPC electric vehicle, which integrates the traditional motor with the hydraulic pump/motor to realize the mutual conversion of electrical energy, mechanical energy, and hydraulic energy. A distribution method for the electro-hydraulic ratio under different working modes is proposed taking the electric peak torque as the optimal target. Compared with the AMESim certified cycle, the results indicate that the MEHPC system can significantly reduce electric peak torque and improve the battery's state of charge (SOC) after the proportional distribution. Simultaneously, the article determines the optimal ratio by multiple optimization objectives with SOC as the constraint. The results illustrate that the phenomenon of torque surge can be reduced under the appropriate proportion, and the battery energy consumption rate is reduced by 33.54% compared to pure electric vehicles. Moreover, the actual driving conditions are analyzed utilizing actual data acquisition and simulation. The results suggest that the peak torque is lower than pure electric vehicles, and the energy utilization is improved substantially with the battery consumption reduced by 20.86%. Therefore, the proposed method combines better energy efficiency, stability, and economic performance, which will be expected to provide a good reference for the development of electro-hydraulic systems.